Real-Time Implementation of GPS Aided Low Cost Strapdown Inertial Navigation System - Sahawneh, Laith Rasmi (2009)
A Master of Science Thesis in Mechatronics Submitted by Laith Rasmi Sahawneh Entitled, "Real-Time Implementation of GPS Aided Low Cost Strapdown Inertial Navigation System," April 2009. Available are both Soft and Hard Copies of the Thesis.